x-3y=7 and 2x-6y=12 solving by elimination

Answers

Answer 1

x-3y=7    2x-6y=12

You can multiply -2 in the first equation like this.

x+6y=7

2x-6y=12

Now you can eliminate 6y and -6y so cross them out and do x-2 which is -1 and 7-12 which is -5 -1/-5 would be .2


Related Questions

The daily supply of oxygen for a particular multicellular organism is provided by 625 square feet of lawn. A total of 5,000 square feet of lawn would provide the daily supplies of oxygen for how many organisms?

Answers

Answer:

5000 square feet of lawn would provide the daily supplies of oxygen for 8 organisms.

Explanation:

 The daily supply of oxygen for a particular multi cellular organism is provided by 625 square feet of lawn

Total area of lawn provided = 5,000 square feet

Number of organism for which provided lawn area supplies oxygen = Total area of lawn provided/ Daily requirement of lawn area for 1 organism.

Number of organism for which provided lawn area supplies oxygen = 5000/625 = 8 organisms.

So 5000 square feet of lawn would provide the daily supplies of oxygen for 8 organisms.

Final answer:

A total of 5,000 square feet of lawn would provide the daily supplies of oxygen for 8 organisms based on the ratio given.

Explanation:

The question can be solved using the concept of ratios. The ratio of lawn to organisms is 625 square feet to 1 multicellular organism. So, if we have 5,000 square feet lawn area, we can find how many organisms it can support by setting up a proportion and solving for the unknown number of organisms.

Let's denote the unknown number of organisms as X. The proportion would then be: 625/1 = 5000/X.

To solve this equation for X, we can cross-multiply and divide. So, X = 5000 / 625 = 8 multicellular organisms.

Learn more about Ratios here:

https://brainly.com/question/32531170

#SPJ3

Solve for: a,b, and c

Answers

a=2

b=6

c=-6

You can use the substitution method to solve.

a plane traveled 580 miles to chicago and back. the trip there was with the wind. it took 5 hours. the trip back was into the wind. the trip back took 10 hours. find the speed of the plane in still air and the speed of the wind.

Answers

If the speed in still air is s, and the wind speed is w,

580/(s+w) = 5

580/(s-w) = 10

s=87

w=29

Final answer:

To determine the speed of the plane in still air and the speed of the wind, we use the distances and times provided to create two equations. Solving this system reveals that the speed of the plane in still air is 87 mph and the speed of the wind is 29 mph.

Explanation:

To find the speed of the plane in still air and the speed of the wind, we can set up a system of equations based on the given information. We'll let p represent the speed of the plane in still air and w represent the speed of the wind.

When the plane travels with the wind, its effective speed is p + w, and the time taken for the trip is 5 hours, covering 580 miles. So, our first equation is:

1) (p + w) * 5 = 580

When the plane returns against the wind, its effective speed is p - w, and the time taken for this trip is 10 hours, again covering 580 miles. Thus, our second equation is:

2) (p - w) * 10 = 580

Solving this system of equations, we'll start by simplifying both:

p + w = 116 (By dividing the first equation by 5)

p - w = 58 (By dividing the second equation by 10)

Now we can add both equations to eliminate w:

2p = 174

Divide by 2 to get the speed of the plane in still air:

p = 87 mph

To find the speed of the wind, substitute the value of p in one of the equations:

87 + w = 116

So, the speed of the wind is:

w = 116 - 87

w = 29 mph

The speed of the plane in still air is 87 mph, and the speed of the wind is 29 mph.

The first number of three consecutive even integers equals the sum of the second and third. Find the three numbers.

If x represents the smallest integer, then which of the following equations could be used to solve the problem?


Answers

The first integer (x) is equal to the consecutive even integers, x+2, x+4.

x = (x+2) + (x+4)

x = 2x + 6

x - 6 = 2x

x = -6 (First integer)


+2

-4 (Second integer)


+4

-2 (Third integer)


Integers: -6, -4, -2

Equation: x = (x+2) + (x+4)

Answer:

2x+2=x+4

Step-by-step explanation:

y=-9x+3 complete the ordered pair

Answers

*(The first order pair)*

[tex]y=-9(0)+3[/tex]                   Substitute [tex]0[/tex] to [tex]y=-9(0)+3[/tex]

[tex]y=0+3[/tex]                        Multiply [tex]-9[/tex] to [tex]0[/tex]

[tex]y=3[/tex]                            Add [tex]3[/tex] to [tex]0[/tex]

*(Answer)*= [tex](0, 3)[/tex]


*(The second order pair)*

[tex]y=-9(3)+3[/tex]                   Substitute [tex]3[/tex] to [tex]y=-9(3)+3[/tex]

[tex]y=-27+3[/tex]                        Multiply [tex]-9[/tex] to [tex]3[/tex]

[tex]y=-24[/tex]                            Subtract [tex]3[/tex] to [tex]-27[/tex]

*(Answer)*= [tex](3, -24)[/tex]


*(The third order pair)*

[tex]30=-9x+3[/tex]                   Substitute [tex]30[/tex] to [tex]30=-9x+3[/tex]

[tex]27=-9x[/tex]                        Subtract [tex]3[/tex] to [tex]30[/tex]

[tex]x=-3[/tex]                           Divide [tex]-9[/tex] to [tex]27[/tex]

*(Answer)*= [tex](-3, 30)[/tex]

Hope this helps

The person who answer: BangtanBoyScouts

Help solve
|m + 3|= 7

Answers

m + 3 = 7

m = 4

m + 3 = -7

m = -10


m = 4, -10

The given equation is |m + 3|= 7. The values of m are 4 and -10.

What does it mean to solve an equation?

An equation represents the equality of two or more mathematical expressions.

Solutions to an equation are those values of the variables involved in that equation for which the equation is true.

The given equation is |m + 3|= 7.

m + 3 = 7

m = 4

m + 3 = -7

m = -10

Hence, m = 4, -10

Learn more about solving equations here:

https://brainly.com/question/18015090

#SPJ2

Im not sure I need help

Answers

[tex]\dfrac{4}{9}-\left|\dfrac{5}{18}\right|=\dfrac{4}{9}-\dfrac{5}{18}=\dfrac{8}{18}-\dfrac{5}{18}=\dfrac{3}{18}=\dfrac{1}{6}[/tex]

A recent nationwide study of myopia (nearsightedness) found that 38.1% of American adults ages 18 to 24 suffer from myopia. Consider two young adults between the ages of 18 and 24, chosen randomly and independently. The probability that neither of them suffer from myopia is

Answers

Final answer:

The probability that neither of them suffer from myopia can be calculated by finding the probability that one individual does not suffer from myopia and then multiplying that probability by the probability that the second individual also does not suffer from myopia.

Explanation:

The probability that neither of them suffer from myopia can be calculated by finding the probability that one individual does not suffer from myopia and then multiplying that probability by the probability that the second individual also does not suffer from myopia.

The probability that one individual does not suffer from myopia is 1 - 0.381 = 0.619. Since the two individuals are chosen randomly and independently, the probability that the second individual does not suffer from myopia is also 0.619.

Therefore, the probability that neither of them suffer from myopia is 0.619 * 0.619 = 0.382161.

evaluate the expression if H=120 and T=12.

Answers

what is the expression


Which calculation can be used to find value of p in the equation p^3=8

Answers

Well, the opposite of an exponent is a square root. However, in this case, it is to the power of 3. So in order to find p, you must do the cube root on both sides in order to get your answer:

[tex]p^3=3[/tex]

[tex]\sqrt[3]{p^3} =\sqrt[3]{8}[/tex]

[tex]p=2[/tex]

If t varies as v, and t = 2 4/7 when v =13/14 , find v when t = 2 1/4

a) 2106/392
b) 13/16
c) 324/52

Answers

Answer : b) 13/16

Given : t varies as v

So t = k v  where k is the constant of proportionality.

t = 2 4/7 when v =13/14. Using these values we find out k

[tex]t = 2\frac{4}{7} =\frac{18}{7}[/tex]

[tex]v =\frac{13}{14}[/tex]

t = k * v

[tex]\frac{18}{7}= k *\frac{13}{14}[/tex]

Multiply by 14/13 on both sides

[tex]\frac{18}{7} *\frac{14}{13} = k *\frac{13}{14}*\frac{14}{13}[/tex]

So  [tex]k =\frac{36}{13}[/tex]

We got the value of k. Now we find v when t = 2 1/4

[tex]t = 2\frac{1}{4} =\frac{9}{4}[/tex]

t = k * v

We know the value of t and k

[tex]\frac{9}{4}= \frac{36}{13}* v[/tex]

Multiply by 13/36 on both sides

[tex]\frac{9}{4} *\frac{13}{36} =\frac{36}{13}*\frac{13}{36}* v[/tex]

So  [tex] \frac{13}{16}= v[/tex]

Option B is correct

A flooring company sells stain-resistant carpets for $2.20 per square foot, and will install the carpet the carpet for an additional fee of $50. A function to model relationship is f(x)=2.20x+50. What is the dependent quantity in this situation?

Answers

2.20x is the dependent quantity. It is DEPENDANT on how much carpet you buy, it changes.

In f(x) = 2.20x + 50 the dependent function is the total cost of flooring the carpet.

What is a function?

A function can be defined as the outputs for a given set of inputs.

The inputs of a function are known as the independent variable and the outputs of a function are known as the dependent variable.

Given, A flooring company sells stain-resistant carpets for $2.20 per square foot and will install the carpet for an additional fee of $50 which is represented by f(x) = 2.20x + 50.

Here dependent variable is f(x) which is the cost of the complete project depending on the square foot.

learn more about functions here :

https://brainly.com/question/12431044

#SPJ2

What is the slope of the line through (-4, 2) and (3, -3)
need answers

Answers

The equation for this is x2-x1/y2-y1 and so you plug in the numbers and get -5/7, and that is your slope.

my tens digit is double my ones digit. i am less then 70 and greater than 60.

Answers

The answer you are looking for would be 63.

63 is greater than 60, but less than 70, and the tens place (6) is double the ones place (3). Thus meaning 63 is the answer.

I hope this helps!

What is the value of n? n–2=(10n+4)/2

Answers

Step 1. Factor out the common term 2

n - 2 = 2(5n + 2)/2

Step 2. Cancel 2

n - 2 = 5n + 2

Step 3. Subtract n from both sides

-2 = 5n + 2 - n

Step 4. Simplify 5n + 2 - n to 4n + 2

-2 = 4n + 2

Step 5. Subtract 2 from both sides

-2 - 2 = 4n

Step 6. Simplify -2 - 2 to -4

-4 = 4n

Step 7. Divide both sides by 4

-1 = n

Step 8. Switch sides

n = -1

Final answer:

To find the value of n, rearrange the equation and simplify to solve for n.

Explanation:

To find the value of n, we need to solve the given equation. First, distribute the 2 on the right side:

n - 2 = 10n + 4

Next, subtract 10n from both sides:

n - 10n - 2 = 4

Combine like terms:

-9n - 2 = 4

Then, add 2 to both sides:

-9n = 6

Finally, divide both sides by -9 to solve for n:

n = -6/9 which simplifies to n = -2/3.

Learn more about Solving Equations here:

https://brainly.com/question/18322830

#SPJ2

what is the intersectionof the set [0,1,5,7] and [0,5,7,9]

Answers

[tex]\{0,1,5,7\}\cap\{0,5,7,9\}=\{5,7\}[/tex]

will someone please help,me with this

Answers

add all of the students together (18+8+22+32) then add the students together who have a car or be in 12th grade or both (8+22+18) ratio car/in 12th grade/ total students (48/80) change to a percent. Hope that helps.

OMG PLS HELP AND NO ABSURD RESPONSES THIS TIME SMH

Answers

The colors on the image should match the correct blank spots on the proof. Please let me know if you disagree or is confused by my choices.

What is the product of -2 1/2 and -3 1/3?

Answers

I put the work so you can see it but the answer is 8 1/3
Final answer:

The product of -2 1/2 and -3 1/3 is 8 1/3. This is calculated by converting mixed numbers into improper fractions and then multiplying. Multiplying two negative numbers gives a positive result.

Explanation:

To compute the product of -2 1/2 and -3 1/3, first convert these mixed numbers into improper fractions.  -2 1/2 can be converted to -5/2 and -3 1/3 is -10/3.  Then, simply multiply these two fractions:

(-5/2) x (-10/3) = 50/6 = 25/3 or 8 1/3 .So the product of -2 1/2 and -3 1/3 is positive 8 1/3. Remember, multiplying two negative numbers results in a positive product.

Learn more about Multiplication of Fractions here:

https://brainly.com/question/23715562

#SPJ2

A boat travels 26 miles up a river in the same amount of time it takes to travel 38 miles down the same river. If the current is 3 mph, what is the speed of the boat in till water?

Answers

Let the speed of the boat in still water = X


The current is 3 mph, so the speed of the boat going upstream would be x-3

Speed of the boat going down stream would be x +3

The trip upstream is 26 / x-3

The trip downstream is 38 / x+3


Set them to equal and solve for x:

26/x-3 = 38/x+3

Multiply both sides by (x+3)(x-3):

38(x-3) = 26(x+3)

Simplify:

38x - 114 = 26x+78

Subtract 26x from each side:

12x -114 = 78

Add 114 to each side:

12x = 192

Divide both sides by 12:

x = 192 / 12

x = 16

The speed is 16 miles per hour.

Final answer:

To determine the boat's speed in still water, an equation is set up that relates the upstream and downstream times, given that the current influences the boat's effective speed by 3 mph. Solving this equation yields a speed of 16 mph for the boat in still water.

Explanation:

To find the speed of the boat in still water, we need to account for the effect of the current on the boat's speed when going up and down the river. Let the speed of the boat in still water be v mph.

When the boat is going upstream (against the current), its effective speed is (v - 3) mph because the current slows the boat down by 3 mph. When the boat is going downstream (with the current), its effective speed is (v + 3) mph because the current speeds the boat up by 3 mph.

Since the boat covers 26 miles upstream and 38 miles downstream in the same time, we can set the time equal for both scenarios:

Time = Distance / Speed

Time upstream = 26 / (v - 3)Time downstream = 38 / (v + 3)

By equating the two times, we get:

26 / (v - 3) = 38 / (v + 3)

To solve for v, cross-multiply and simplify:

26(v + 3) = 38(v - 3)

26v + 78 = 38v - 114

12v = 192

v = 192 / 12

v = 16 mph

Therefore, the speed of the boat in still water is 16 mph.

11.6 ; 11 ; 11.06 ; 11.56 least to greatest

Answers

11

11.06

11.56

11.6

is what you are looking for

The order would go 11; 11:06; 11.56; 11.6

What is the unit rate of a 1.25L Coca Cola that cost $1.29

Answers

a 1.25L Coca Cola that cost $1.29

Unit rate means we need to find the rate of 1 liter of Coca Cola

1.25 L Coca Cola =  $1.29

1 L of Coca Cola = ?

To find 1 liter of Coca cola divide the cost by liter, so we divide 1.29 by 1.25

[tex]\frac{1.29}{1.25}[/tex]

1.032

So the cost of 1 liter of Coco Cola = $1.032


PLEASE HELP ME
solve for x. −2(x+13)+9x=4 ​

Answers

First open the bracket by multiplying with -2

-2x - 26 +9x = 4

Solving like terms

7x - 26 = 4

Adding 26 to both sides

7x - 26 +26 = 4+26

7x = 30

X = 30/7



[tex]-2(x+13)+9x=4\\\\-2x-26+9x=4\\\\7x=30\\\\x=\dfrac{30}{7}[/tex]

What is one sixth plus one half

Answers

The answer you are looking for is 2/3.

When adding or subtracting fractions, they must have the same denominator. To make 1/6 and 1/2 have the same denominator, you must multiply 1/2 by 3/3 straight across. This gives you 3/6 which you can now add 1/6 to to get 4/6. 4/6 can be simplified down to 2/3 by dividing by 2/2. Thus making 2/3 the answer.

I hope this helps!

To add one sixth and one half, convert them to have the same denominator, resulting in 1/6 plus 3/6 (or 4/6), which simplifies to two thirds.

When adding fractions such as one sixth and one half, it's essential to have a common denominator. To find a common denominator for 1/6 and 1/2, we need to think about the multiples of both 6 and 2. The smallest common multiple is 6, so we convert 1/2 into a fraction that has 6 as the denominator. The fraction 1/2 is equivalent to 3/6 since 2 multiplied by 3 equals 6. Now we can add the fractions:

Convert 1/2 to 3/6.Add 1/6 to 3/6, which equals 4/6.Simplify the fraction 4/6 to its lowest terms, which is 2/3.

Therefore, one sixth plus one half is equal to two thirds.

if 12 men are needed to run 4 machines,how many men are needed to run 20 machines?

Answers

12/4=x/20

x=60

60 people are needed

4x3=12 right. Then 20x3=60.

at a chess tournament the number of competitors in each round is 50% of the number of competitors in the previous round. What type of relationship most appropriately models this situation?

exponential growth
linear increase
linear decrease
exponential decay

Answers

This is an exponential decay because it decreases by 1/2 each time

Answer:

The answer is exponential decay.

Step-by-step explanation:

At a chess tournament the number of competitors in each round is 50% of the number of competitors in the previous round.

So, the relationship that most appropriately models this situation is exponential decay.

Exponential decay is the process of reducing any given amount by a fixed or gradual percentage rate over a period of time.

It can be written like [tex]y= a(1-b)^{x}[/tex]

Where, y is the final amount

a is the original amount

b is the decay factor

x is the amount of time that has passed.

There are two connected gears. One has 60 teeth and it makes 50 complete revolutions in a minute. How many complete revolutions will the second gear complete, if it has 40 teeth?

Answers

Answer:

The second gear will complete 75 complete revolutions

Step-by-step explanation:

- There are two connected gears

- One has 60 teeth and the other has 40 teeth

- The two gears have different revolutions depends on the number of

  their teethes

- They do the same job

- The relation between them is

   [tex]n_{1}*c_{1}=n_{2}*c_{2}[/tex], where n is the number of the complete

   revolutions and c is the number of the teeth

- The gear which has less teethes makes more complete revolutions

∵ [tex]n_{1}[/tex] = 50

∵ [tex]c_{1}[/tex] = 60

∵ [tex]c_{2}[/tex] = 40

- Substitute these values in the rule below

∵ [tex]n_{1}[/tex] × [tex]c_{1}[/tex] = [tex]n_{2}[/tex] × [tex]c_{2}[/tex]

∴ 50 × 60 = [tex]n_{2}[/tex] × 40

∴ 3000 = 40 [tex]n_{2}[/tex]

- Divide both sides by 40

∴ [tex]n_{2}[/tex] = 75 complete revolutions

The second gear will complete 75 complete revolutions

(x³-3x²+3x-2)÷(x²-x+1)

Answers

Answer: ⇒ =x-2

________________________________________________________

Step-by-step explanation:

Compute [tex]\frac{x^3-3x^2+3x-2}{x-2}[/tex] to get the rest of the equation.

[tex]\frac{(x-2)(x^2-x+1)}{x^2-x+1}[/tex]

Then you had to cancel by the common factor of [tex]x^2-x+1[/tex]

[tex]=x-2[/tex]

______________________________________________________

Hope this helps!

Thank you for posting your question at here on brainly.

Have a great day!

____________________________________________________

what is the area of the square

Answers

52 feet.

13 x 4 because its all the same length.

I need help on this problem ASAP pls help me.

Answers

The first one on the right is the answer for 1/2 of 2/4 and the second one on the right is the one for 2/3 of 3/8

Okay so fiquring out 1/2 of 1/4 is simple got to the third diagram since it has been cut to match the 1/2.  1/3 of 3/8 would be the first diagram since the squares have been sliced in half.

Other Questions
PLEASE HELPPPPPP!! WILL GIVE BRAINLIEST ASAPPPPPPPPPPPPHow did the ideas of Jean-Jacques Rousseau compare to those of John Locke?Both believed in the theory of a social contract.Both believed that individuals were corrupted by society.Both condemned the idea of individuals having the rights of life, liberty, and property.Both were fearful of revolution. Drag phrase that means uniform into the box to complete the sentence What is the percent increase from 13 to 14 PLEASE ANSWER!!Look at the diagram shown below.Which of these locations on Earth will most likely experience the highest tide?ABCD Is it who or whose to this sentence : Whos/whose muddy foot prints are those ??? Which activity is the best example of a paleolithic lifestyle A.hunting mammothsB.herding sheepC.planting barley D.growing vegetables Roberto has a sample of an unknown liquid. The label in the bottle of the sample indicates that the liquid has a mass of 117 grams and a volume of 15 cubic centimeters. What is the liquid in the bottle? gasoline milk water mercury need help with this math y= 2+4.3x when x= -6 Jay needs 19 quarts more paint for the outside of his barn than for the inside.If he uses 107 quarts in all,how many gallons of paint will be used to paint the inside of the barn? Interpret this graph. Explain the relationship between the variables (cost of pizza and number of toppings). Which of the following is arguably at the root of all violence between Native Americans and the U.S. military? inability of both parties to follow through on treaties misunderstanding of negotiated and agreed upon terms the forced and repetitive relocation of Native Americans an unbalanced political structure of authority I'm so confused please help What are the first four terms of the sequence shown below?an = 2^nA.1, 2, 4, 8B.2, 4, 6, 8C.2, 4, 8, 16D.1, 8, 27, 256 Are -3.9 and -0.99 on the same side or the opposite side of zero ? If the velocity of a car is 45 km/h west, how far can it travel in 0.5 hours? Shays's Rebellion in western Massachusetts showed that the national government needed additional powers to address some urgent issues. Which issues were they?A.slavery and individual libertiesB.domestic economy and securityC.foreign security and westward expansionD.foreign trade and defenseE.interstate commerce and state boundaries Socialists wanted the government to take over the business is that affected most citizens, like railroads, electric power, and telephones. Socialist wanted to re-organize society in new ways. TrueFalse The only way an object's speed or direction of motion can be changed is if a(n) _______ force acts on it. Please help I really dont understand